Investigation of the Antioxidant and Hepatoprotective Potential of Hypericum mysorense - Raghu C. Hariharapura; Ramamurthy Srinivasan; Godavarthi Ashok; Santoshkumar H. Dongre; Hitesh V. Jagani; Pottekkad Vijayan (MDPI AG, 2014)
Background: Hypericum is a well-known plant genus in herbal medicine. Hypericum mysorense (Family: Hypericaceae), a plant belonging to the same genus, is well known in folklore medicine for its varied therapeutic potential. Objective: The aim of the present study was to investigate the different parts of the plant for antioxidant and hepatoprotective properties. Materials and Methods: The methanol extracts of Hypericum mysorense prepared from various parts of the plant were tested in vitro for their free radical scavenging activity against ABTS• (diammonium salt), DPPH• (1,1-diphenyl-2-picrylhydrazyl), NO•, O2•− and •OH radicals, using standard systems of assays. The total antioxidant capacity, total phenolic and total flavonoid content of the extracts were analyzed. Further, the leaf and flowering top extracts were tested for their in vivo antioxidant and hepatoprotective activities on Wistar rats using a carbon tetrachloride-induced hepatic injury model. Results: The leaf and flowering top extract showed potent antioxidant activity and also possessed highest total phenolic and flavonoid content. The antioxidant activity and the total phenolic and flavonoid content present in these extracts showed a good correlation. The leaf and flowering top extracts at 200 mg/kg restored aspartate amino transferase (ASAT), alanine amino transferase (ALAT), alkaline phosphatase (ALP), total bilirubin and protein levels significantly in CCl4-intoxicated rats. The tested extracts also showed a significant (p < 0.001) reduction in 2-thiobarbituric acid reactive substance (TBARS) levels with an increase in SOD and CAT levels. The histopathology of liver did not show any toxicity after the treatment with the extracts. The active extracts were standardized using two marker compounds, hyperoside and rutin, which were isolated from the plant by HPLC. HPLC studies revealed that the maximum concentration of hyperoside and rutin is present in the flowering top extract.